The stressed subject: Lack, empowerment and liberation - Driver, Michaela (2014)
The study develops a psychoanalytic perspective on the stressed subject at work. Its focus is on how this subject is continually reconstructed at the interstice of a lack of having and a lack of being. Drawing on the analysis of empirical material consisting of 52 narratives of stress, it examines how individuals construct selves by drawing on stress discourse in both alienating and liberating ways. Specifically, it examines how stress is an imaginary construction of the self and how this subjugates individuals to the power of the imaginary. It also examines how such constructions are invariably disrupted by unconscious desire and how narrating one's stress provides opportunities to experience empowerment and liberation. Implications of this perspective for our understanding of the stressed subject are discussed. - Reproduced.
Keywords: Organizational disease